2015
DOI: 10.1007/s00405-015-3610-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical findings and auditory performance after cochlear implant revision surgery

Abstract: The objective of this study was to review cochlear reimplantation outcomes in the tertiary hospital and analyze whether facts such as type of failure, surgical findings, or etiology of deafness have an influence. A retrospective study including 38 patients who underwent cochlear implant revision surgery in a tertiary center is performed. Auditory outcomes (pure tone audiometry, % disyllabic words) along with etiology of deafness, type of complication, issues with insertion, and cochlear findings are included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 25 publications
5
30
2
1
Order By: Relevance
“…When pooled, these studies accounted for 21,301 cochlear implants, 1,277 reimplants, and an overall reimplantation rate of 6.0% (range, 0.47%-6.87%) (Table V). 4,5,[8][9][10][11][12][13][14][15]17,18,[20][21][22][23][24][25][26][27][28][29] Studies ranged in the duration of data collection from 7 to 30 years and ranged in primary implant numbers from 212 to 3,417. The pooled medical failure rate was 2.1%, and the device failure rate was 3.6%.…”
Section: Resultsmentioning
confidence: 99%
“…When pooled, these studies accounted for 21,301 cochlear implants, 1,277 reimplants, and an overall reimplantation rate of 6.0% (range, 0.47%-6.87%) (Table V). 4,5,[8][9][10][11][12][13][14][15]17,18,[20][21][22][23][24][25][26][27][28][29] Studies ranged in the duration of data collection from 7 to 30 years and ranged in primary implant numbers from 212 to 3,417. The pooled medical failure rate was 2.1%, and the device failure rate was 3.6%.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the surgically oriented reports, there is a paucity of studies that examine functional outcomes of reimplantation surgery. In a recent study by Manrique-Huarte, Huarte, & Manrique (2016) , of 962 pediatric and adult patients implanted over a 23-year period, 38 patients required reimplantation (28 children, 10 adults). The authors report that aided pure-tone hearing thresholds improved in 44% of the reimplanted patients, with 11% showing no change in their thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…Electrode migration or partial insertion during the first surgery could be the causes of no improvement in speech perception [10]. After the revision surgery, it could be confirmed that the electrode did not migrate outside the cochlea and that it was fully inserted (first white marker was seen in the round window).…”
Section: Discussionmentioning
confidence: 97%
“…Following this concept, an electrode afterload seems attractive and logical when hearing loss progresses and greater insertion depths are required for better outcomes. Also, in the case of postoperative hearing loss, the electrode can be further inserted, so the patients can benefit from greater cochlear coverage using electric stimulation only [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation